Pulsiones nerviosas de un orden craquelado: desafíos, caballerosidad y esfera política (Perú, 1883-1960) - Chocano, Magdalena (2011)
Through an examination of several episodes we will study the persistence of the practice of duels and honor fights in the political atmosphere of republican Peru. Each episode reveals different interests which aimed to maintain the duel as a mechanism to avoid or limit freedom of expression or debate. A good number of members of the political and social elite defended dueling in the press as an acceptable practice even though it was penalized by government law. This attitude can be seen as concomitant with repression of political organizations in the country and the maintaining of a type of patriarchal domination which called for the prolonged exclusion of women from citizenship.